Freshwater Sediment Microbial Communities Are Not Resilient to Disturbance From Agricultural Land Runoff - Beattie, Rachelle E.; Bandla, Aditya; Swarup, Sanjay; Hristova, Krassimira R. (Frontiers in Microbiology, 2020)
Microorganisms are critically important for the function of surface water ecosystems but are frequently subjected to anthropogenic disturbances at either acute (pulse) or long-term (press) scales. Response and recovery of microbial community composition and function following pulse disturbance is well studied in controlled, laboratory scale experiments but is less well understood in natural environments undergoing continual press disturbance. The objectives of this study were to determine the drivers of sediment microbial compositional and functional changes in freshwaters receiving continual press disturbance from agricultural land runoff and to evaluate the ability of the native microbial community to resist disturbance related changes as a proxy for freshwater ecosystem health. Freshwater sediments were collected seasonally over one year in Kewaunee County, Wisconsin, a region impacted by concentrated dairy cattle farming, manure fertilization, and associated agricultural runoff which together serve as a press disturbance. Using 16S rRNA gene amplicon sequencing, we found that sediments in locations strongly impacted by intensive agriculture contain significantly higher abundances (p<0.01) of the genera Thiobacillus, Methylotenera, Crenotrhix, Nitrospira, and Rhodoferax compared to reference sediments, and functions including nitrate reduction, nitrite reduction, and nitrogen respiration are significantly higher (p<0.05) at locations in close proximity to large farms. Nine species-level potential human pathogens were identified in riverine sediments including Acinetobacer lwoffi and Arcobacter skirrowii, two pathogens associated with the cattle microbiome. Microbial community composition at locations in close proximity to intensive agriculture was not resistant nor resilient to agricultural runoff disturbance within five months post-disturbance but did reach a new, stable microbial composition. From this data, we conclude that sediment microbial community composition is sensitive and shifts in response to chemical and microbial pollution from intensive agriculture, has a low capacity to resist infiltration by non-native, harmful bacteria and, overall, the natural buffering capacity of freshwater ecosystems is unable to fully resist the impacts from agricultural press disturbance.